Study of ISFET sensitivity to pH variations using Silvaco TCAD - Nur Afiqah Hani Senin; Anis Suhaila Mohd Zain; Fauziyah Salehuddin; Hazura Haroon; Ahmed Musa Dinar; Norwahidah Abdul Karim (Universitas Ahmad Dahlan, 2024)
Chemical sensors are increasingly used in healthcare because of their small size, durability, low resistance, and quick reaction time. This research aims to develop a pH biosensor utilizing an ion-sensitive field-effect transistor (ISFET) simulated with Silvaco technology computer-aided design (TCAD) software. The pH range of operation for the ISFET is 2 to 12. Sensitivity was evaluated based on the critical pH value and threshold voltage (Vth) parameters across different gate channel lengths (250 nm, 200 nm, and 50 nm) and sensing membrane thicknesses (3 nm, 10 nm, and 20 nm). The sensitivity of different materials to pH levels was measured. Titanium dioxide (TiO2) had the highest sensitivity at 57.98 mV/pH, followed by hafnium (IV) oxide (HfO2) at 57.46 mV/pH, tantalum pentoxide (Ta2O5) at 57.36 mV/pH, aluminium oxide (Al2O3) at 55.05 mV/pH, and silicon nitride (Si3N4) at 54.75 mV/pH. Notably, TiO2 with a 200 nm gate channel length and a 3 nm sensing membrane thickness demonstrated the highest sensitivity. These findings highlight the potential of ISFETs, particularly those with TiO2 sensing membranes, as robust and precise pH monitoring platforms in the biomedical industry.